2012
DOI: 10.1016/j.otsr.2012.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Teleconsultation in paediatric orthopaedics in Djibouti: Evaluation of response performance

Abstract: III, prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 6 publications
0
28
0
1
Order By: Relevance
“…Another class in this group was teleconsultations that were established between physicians of developing countries and experts from developed countries. Requesting countries in one third of the articles in this class were from Africa varying in medical fields like pediatrics ( 27 , 28 ), orthopedics ( 4 ), surgery ( 29 ), and infectious disease ( 30 ). In addition, experiences of teleconsultation between Antarctic stations with their supporting countries ( 31 - 33 ) or geographically remote islands with other countries were reported ( 34 - 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another class in this group was teleconsultations that were established between physicians of developing countries and experts from developed countries. Requesting countries in one third of the articles in this class were from Africa varying in medical fields like pediatrics ( 27 , 28 ), orthopedics ( 4 ), surgery ( 29 ), and infectious disease ( 30 ). In addition, experiences of teleconsultation between Antarctic stations with their supporting countries ( 31 - 33 ) or geographically remote islands with other countries were reported ( 34 - 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…L'idée est de tendre vers une finalisation de la prise en charge chirurgicale en fin d'hospitalisation initiale. La téléméde-cine représente une aide validée pour obtenir l'expertise nécessaire à la planification du projet thérapeutique [13].…”
Section: Discussionunclassified
“…Other studies have demonstrated the effectiveness of similar programs for other medical specialties [10,11]. In the future, the development of a civilian medical toxicology teleconsultation service to assist both local and volunteer physicians in locations with limited subspecialty care may aid in reaching those in greatest need.…”
Section: Discussionmentioning
confidence: 99%